Addressing the Haemolytic Disease of the Fetus -Arun To Ba Eje Omo Ninu Oyun Je amongst Female Residents in Imota - Akintayo, Atinuke Olubukade; Aondover, Eric Msughter (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
Assessing pregnant women’s awareness of Rh incompatibility is crucial to avoiding and treating issues related to this illness, as the rate of miscarriages among young women is alarming and requires immediate care. Because of the kind of Rhesus factor they have, women in Nigeria miscarry every three months. Due to a lack of knowledge, some of these mothers are not aware of this fetal hemolytic illness. Some women relate the health event to spiritual conditions, beliefs and traditions. Medical research has demonstrated that the primary cause of the miscarriages that occur every three months of pregnancy is the Rhesus factor that certain women possess. This study aimed at assessing the levels of awareness and knowledge of the Rhesus factor among women in Imota, Lagos State, to determine the extent to which health institutions' communication strategies contribute to women's understanding and awareness of Rh factor, to ascertain the knowledge level of Rh factor, its implications in pregnancy and to determine how well media advocacy works to inform female residents of Ikorodu Local Government Areas, which include Imota, Isiu, Ijede, and Bayeku. The results showed that female residents of the selected areas in Lagos State, have not received enough media attention regarding the fetal hemolytic illness. The findings showed that, though the level of awareness of the Rhesus factor among the women in the State was high, the knowledge level of the Rh compatibility issues on maternal and child health and its implications in pregnancy was low.